Analysis of the Influence Principal's Ethics Policy on the Quality of Islamic Education at SMPN 2 Bayan - Kahar, Abdul Manan; Imtihan, Nurul; Malik, Abdul (Tadbir : Jurnal Studi Manajemen Pendidikan, 2024)
The aim of this research is to explain the influence of principal policies on the quality of Islamic education at SMPN 2 Bayan. This research uses a quantitative type with an analytical design. The population of this study was all teachers and students of SMPN 2 Bayan and the sample was 10 teachers and 15 students. The sampling technique used is random sampling. Data collection techniques through observation with questionnaire instruments for Islamic education policy and quality. The data analysis technique uses the t test and or F test. The results of the research show that there is an influence of the principal's policy on the quality of Islamic education at SMPN 2 Bayan as seen from the significant value obtained in the t test and F test .000b which is smaller than 0.05. This means Ha is accepted and Ho is rejected. Researchers want to see further whether these influences occur simultaneously or not. To find out, you can use the F test data in the Anova table. The F test is a statistical method used to compare variations between two or more groups of data. The F test is used to see whether the relationship or influence of data occurs simultaneously or not.